FACING GLOBAL CHALLENGES: INFORMATION TECHNOLOGY PROFESSION ETHICS BASED ON PAI IN VOCATIONAL SCHOOLS - In’ami, Moh.; Arisanti, Nyimas Depi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article discusses the urgency of integrating professional ethics in Information Technology (IT)based on Islamic education in vocational schools (SMK). The study aims to assess the influence of Islamic education on shaping professional ethics within the IT field. Using a qualitative approach, data is collected from teachers and curriculum experts and analyzed to explore the integration of ethics in IT education. The findings reveal that Islamic education contributes significantly to ethical behaviour in IT practices, promoting honesty, integrity, and accountability. The study suggests enhancing the curriculum by incorporating Islamic values better to prepare students for ethical challenges in the digital era.